Pengaruh Pengembangan Pegawai terhadap Kinerja Pegawai dengan Disiplin Pegawai sebagai Variabel Intervening pada Dinas PUPR Kota Jambi - Adinda Zuraida Mahdafiqia,; Sumarni Sumarni,; Rts. Ratnawati, (Journal of Management and Creative Business, 2024)
The agency's success can be gauged by the caliber of its workforce. Employee development is a pivotal aspect of human resources, serving as a crucial tool for honing abilities and skills to enhance employee performance. Moreover, work discipline stands out as a pivotal factor influencing employee performance, especially within governmental contexts which demand high standards. This study aims to ascertain the impact of employee development on employee performance, with work discipline serving as an intervening variable in the Jambi City Public Works and Spatial Planning (PUPR) Office. The research employs a quantitative descriptive method. Findings reveal a significant positive correlation between employee development and employee performance. Additionally, employee development significantly enhances work discipline, which in turn positively impacts employee performance. Furthermore, employee development significantly enhances employee performance through the intermediary of work discipline.